Slow release boron micronutrients from pelletized borates of the northwest of Argentina - Flores, Horacio Ricardo (2006)
The production of slow release boron micronutrients in water for agricultural fertilizers is presented in this paper. Agglomeration, pelletizing and sinterization techniques are appropriate for manufacturing particles whose dissolution rate can be controlled through their size and chemical composition, according to a selected feeding. The results of boron dissolution in water from pellets made by feeding calcinate colemanite, natural mixtures of tyncal-ulexite, mixtures of calcinate colemanite-calcinate ulexite to a pelletizer disk, as well as the size of pellets and the hardening temperature are analyzed. Pellets made up on feeding calcinate colemanite (700°C) and calcinate tyncal-ulexite perform better properties for slow release boron micronutrients, restricting the concentration in water around 30 ppm. © 2005 Elsevier Ltd. All rights reserved.